Production Fruitghurt From Watermelon Skin With The Addition Of Dragon Fruit Extract As A Natural Colorant - Hamsina Hamsina; Sonia Sonia; Fitri Ariani; Andi Zulfikar Syaiful; M. Tang; Ridwan Ridwan; Hermawati Hermawati; Al Gazali; Andi Abriana; Nani Anggraini; Ruslan Hasani (Universitas Negeri Semarang, 2023)
This study aimed to determine the optimum formulation of fruitghurt from the white layer of watermelon skin with the addition of dragon fruit extract and to analyze the effect of adding dragon fruit extract to pH, lactic acid levels, vitamin C and fruitghurt acceptability from the white layer of watermelon skin. This research method consisted of 5 stages, namely making watermelon skin filtrate, making watermelon extract, making dragon fruit extract, making fruitghurt and incubation (fermentation). In this study, 4 formulations were carried out with different proportions of adding dragon fruit extract. Formula A (100 ml of watermelon skin filtrate, 15 ml of watermelon extract, 0 ml of dragon fruit extract, 11.5 grams of skim milk, 11.5 grams of sugar, 23 grams of plain yogurt), formula B (100 ml of skin filtrate, 15 ml of watermelon extract, 3.5 ml dragon fruit extract, 11.5 grams skim milk, 11.5 grams sugar, 23 grams plain yogurt), formula C (100 ml watermelon peel filtrate, 15 ml watermelon extract, 6.5 ml extract dragon fruit, 11.5 grams of skim milk, 11.5 grams of sugar, 23 grams of plain yogurt), formula D (100 ml of watermelon skin filtrate, 15 ml of watermelon extract, 9.5 ml of dragon fruit extract, 11.5 grams of milk skim, 11.5 grams of sugar, 23 grams of plain yogurt). The sample tests that have been made include the pH test, lactic acid level test, vitamin C level test, and organoleptic test. The test data were analyzed statistically by using Analysis of Variance (ANOVA) and Ducans multiple Range Test (DMRT). The results obtained were the addition of dragon fruit extract had a significantly different effect on pH, lactic acid levels, vitamin C levels, taste, aroma, color, but had no significant effect on the texture of the fruitghurt produced. The optimum formulation obtained was in treatment D with a pH value (4.57), lactic acid content (2.04%), vitamin C content (0.031%), taste test 2.72 (somewhat like), color test 4.88 (like very much), texture test 4.08 (like), and aroma test 3.48 (like)